EFFECT OF DEM RESOLUTION ON EROSION IN BATANG KURANJI WATERSHED - Syofyan, Elvi Roza; -, Bambang Istijono; -, Amrizal Saidi; -, Revalin Herdianto (Jurnal Ilmiah Poli Rekayasa, 2020)
Batang Kuranji Watershed is one of the region river at Indragiri - Akuaman with a total area of Watershed 224.7 km2 consisting of Batang Sungai Sapiah Sub Watershed, Batang Danau Limau Manih Sub Watershed, Batang Sungkai Sub Watershed, Batang Bukik Tindawan Sub Watershed and Batang Padang Janiah Sub Watershed. Batang Kuranji flows from upstream of the Bukit Barisan with the highest elevation + 1,605 meters above sea level at the peak of Bukit Tinjau Laut and empties into the Padang beach with a main river length of ± 32.41. DEM has an influence on the results of land erosion by affecting the slope accuracy. The higher the DEM resolution, the more precise the results of the soil erosion simulation. With the Musle method the rate of erosion occurs in the Batang Kuranji watershed, with DEM data of 8m and land cover in 2017, an erosion rate of 23.91 tons / ha / year is classified in hazard class II (light), DEM data of 30m erosion rate is 7. 70 tons / ha / year are classified in hazard class I (very mild), with DEM data of 90m erosion rate of 4.54 tons / ha / year classified in hazard I class (very light). It can be seen that the higher the DEM resolution, the more accurate the erosion rate calculation in the watershed.